Systemic ventricular function in Fontan patients at rest and after exercise at altitude - Quante, Hannah; Müller, Nicole; Härtel, Julian Alexander; Jung, Thomas; Manunzio, Ursula; Breuer, Johannes; Herberg, Ulrike (Frontiers in Pediatrics, 2023)
Objective: Physical activity at high altitude is expected to pose risks for patients with Fontan circulation and to impair systemic ventricular function. This study aims to determine the effect of high-altitude hypoxia on ventricular function in Fontan patients at rest and after exercise. We hypothesize that systemic ventricular function deteriorates under hypoxic conditions in Fontan patients. Methods: In this prospective study, 21 Fontan patients (NYHA class I-II) and 21 age-, gender- and body mass index-matched healthy controls were enrolled (median age 17.9 and 16.9 years). Transthoracic echocardiography was performed at rest, after peak (PE) and after continuous exercise (CE) in normoxia and hypoxia at simulated altitude (2,500 m above sea level). The effect of hypoxia on echocardiographic parameters was quantified by linear mixed-effects models and the difference between normoxia and hypoxia (Δ= hypoxia-normoxia). Results: At rest, cardiac output (CO) estimated by outflow tract velocity time integral x heart rate and annular plane systolic excursion (APSE) were lower in hypoxia compared to normoxia in Fontan patients (CO: Δ= -12.0%, n.s.; APSE: Δ= -9.6%, p<0.001), an increase was observed in controls (CO: Δ= 8.5%, n.s.; APSE: Δ= 2.5%, n.s.). Other parameters of systolic and diastolic function did not show relevant changes. After exercise under hypoxic conditions, Fontan patients did not show relevant deterioration of systolic function compared to normoxia. Late, active diastolic filling reflected by A-wave velocity remained unchanged in Fontan patients, but increased in controls. Under hypoxic conditions, CO and workload were higher after CE than PE in Fontan patients (CO: PE Δ=1530 vs. CE 1630), whereas controls showed higher work load and CO estimates after PE than CE as expected (CO: PE Δ= 2302 vs. CE 2149). Conclusion: Fontan patients clinically tolerated short-term altitude exposure up to two hours and exercise and showed no consistent deterioration of systolic systemic ventricular function, but parameters of myocardial contractility, heart rate and cardiac output did not increase as observed in controls. This is likely to be multifactorial and may include intrinsic cardiac dysfunction as well as preload inadequacy and the lack of augmented atrial contraction. CE may be better tolerated than PE.